The Effects of Short-Chain Fatty Acids in Urological Diseases - Hee Jo Yang; Doo Sang Kim (Urogenital Tract Infection)
The gut microbiome, believed to serve as a second genome within the human body, is involved in the regulation of several metabolic processes. These include human gene expression, development, nutrition and homeostasis. Dysbiosis, is an imbalance in the gut microbiome, which is known to be associated with various disease conditions such as Crohn's disease and Clostridium infections. The gut microbiota communicates with the host through a variety of biomolecules, nutrient signal-independent pathways, and epigenetic mechanisms. The gut microbiota supports the digestion and absorption of food, metabolizes fiber into bioactive short-chain fatty acids (SCFA), produces vitamins and nutrients, maintains gut integrity, and modulates host immunity. Among the above, there has been great interest in SCFA in microbiome research due to its beneficial effects on the intestinal barrier function and systemic anti-inflammatory effects. Recent reports have also indicated the role of SCFA in obesity, insulin resistance, and type 2 diabetes. While SCFA are associated with reduced risk of various diseases, dysbiosis and altered SCFA fermentative pathways could result in disease. This article is a review on the role of SCFA in urological diseases.